Financial and Monetary Stability Aspects of Global Stablecoins - Stefan Schäfer; Oliver Read (Credit and Capital Markets – Kredit und Kapital, 2020)
Global stablecoins (GSCs) like Facebook's Libra could prove much more instable than they might appear at first sight. Not only can their exchange rates against individual fiat currencies fluctuate substantially; theoretically, they also have the potential to replace national currencies, constitute "digital currency areas" and become the basis of a two-tier banking system with one and more GSC issuers, on the one hand, and, on the other hand, commercial banks that can create GSC deposit money. Against that background, all steps taken so far by supervisors and central banks can only be the starting point of what is necessary to effectively regulate the new normal of the world of money that is emerging.
Keywords: E42; F65; G28; K24; 330; Stablecoins; Libra; Crypto-Assets; Virtual Assets; Blockchain